Impact of clinical supervision of health professionals on organizational outcomes: a mixed methods systematic review protocol. Issue 1 (23rd January 2020) - Martin, Priya; Lizarondo, Lucylynn; Kumar, Saravana; Snowdon, David
ABSTRACT: Objective: The objective of this review is to develop an aggregated synthesis of qualitative and quantitative reviews to derive recommendations for policy and practice relevant to clinical supervision (CS). Introduction: Clinical supervision is a process where supervisors and supervisees engage in guided evaluation and reflection on current practice to enhance future practice. Recent studies have demonstrated the positive impact of CS on patient outcomes; however, the impact of CS on organizational outcomes is less clear. Therefore, this review will investigate organization outcomes and how health practitioners experience and view CS. Inclusion criteria: This review will consider quantitative and qualitative studies on health professional supervisees in nutrition and dietetics, occupational therapy, physiotherapy, psychology, podiatry, social work, speech pathology and exercise physiology in hospitals and community settings. The quantitative component will include studies on the effects of CS based on staff retention and recruitment, intent to stay, intent to leave, job satisfaction and quality of work life, burnout and absenteeism. The qualitative component will consider studies that explore health professional supervisees' experiences on CS related to organizational outcomes. Methods: CINAHL, Embase, PubMed, PsycINFO, PEDro and Scopus will be searched for studies published in English, without a date limit. Both quantitative and qualitative studies will be screened for inclusion and critically appraised for methodological quality, and both types of data extracted using JBI tools for mixed methods systematic reviews. A convergent segregated approach to synthesis and integration will be used. The findings of each single method synthesis will be configured according to JBI methodology.